Complete plastid genome of Astragalus membranaceus (Fisch.) Bunge var. membranaceus. Issue 1 (1st January 2016) - Wang, Bin; Chen, Haimei; Ma, Huiping; Zhang, Hui; Lei, Wanjun; Wu, Wuwei; Shao, Junjie; Jiang, Mei; Zhang, Hui; Jia, Zhengping; Liu, Chang
Abstract: The complete nucleotide sequence of the Astragalus membranaceus (Fisch.) Bunge var. membranaceus chloroplast genome was reported and characterized in this study. The chloroplast genome is a circular molecule of 123623 bp that belongs to the inverted repeat-lacking clade (IRLC). It comprises 110 genes, including 76 protein-coding genes, four unique rRNAs and 30 tRNAs. Similar to the plastomes of A. membranaceus (Fisch.) Bunge var. mongholicus (Bunge) P. K. Hsiao and other closely related species, rpl22 and rps16 are absent. The phylogenetic analysis of 67 proteins from 29 chloroplast genomes belonging to IRLC provided strong support for the non-monophyly of Galegeae. This genome has provided a wealth of information for distinguishing varieties of A. membranaceus .